Old-New Challenges? Poverty and Menstruation: Young Girls and Women in the Mirror of Disadvantaged Situation (European Journal of Marketing and Economics, 2021)
Disadvantaged situation means not just a kind of negative social phenomenon, but its effects manifesting on the economic and social fields are also significant. Regarding its complexity, a holistic view is necessary to approach it, and explore the developed situation, define solution proposals, promote a better quality of life and finally, to monitor prevention processes and revise the proposals if necessary. In case of disadvantaged situation, the involvement of children and women requires special attention in all aspects. The Creative Region research group launched its various research in the multi-stage research of the Higher Education Institutional Excellence Program (in Hungarian: Fels?oktatási Intézményi Kiválósági Program, FIKP) started in 2018 on the University of Miskolc, in which the staff of the Faculty of Health got the opportunity to conduct the comprehensive health mapping of the rural population with the involvement of 25 settlements. Based on the results of the FIKP research, it has been supported from more approaches that disadvantaged situation and deprivation can significantly determine the health behaviour, health consciousness and future life prospects of people living there. The comprehensive research examined the characteristics of the health status of people living in disadvantaged settlements along different dimensions. Getting to know the mental health of young girls and the issue of menstruation days among both them and the adult female population were essential elements of the research. During data recording in 2018 with student girls under the age of 14, we experienced in a high number that the girls’ mental well-being was not ideal, and this also manifested in mild to moderate depression at more of them. The presence of domestic violence affecting them is also not negligible in the region. Our research performed in 2019 also supports that anxiety and the feeling of shame appear strongly among young girls on menstruation days as well, and a certain level of the omission of menstruation hygienic products can also be experienced in the region. Data collection performed in 2020 focused on the adult female population in which we experienced the similar phenomena as in case of young girls. In connection with showing the direction of the areas to be improved and defining the promoting prevention health promotion advice, we should have had to strive for adapting to the population’s demands and the professionals’ flexibility which support the more favourable acceptance of the proposals. The significance of individual care, individual competence improvement and personalized counselling and help is indispensable.
Keywords: poverty, disadvantaged situation, young girls, women, menstruation